An updated bird checklist for Banke National Park and Buffer Zone, Nepal - Inskipp, Carol; Giri, Tikaram; Shahi, Ram; Poudyal, Laxman Prasad (Nepalese Journal of Zoology, 2024)
A seven-day bird survey Banke National Park and Buffer Zone (BaNPBZ) was carried out in March 2024, followed by a desk study extracting records from eBird and Annual Waterbird counts. These records were used to compile an updated checklist for BaNPBZ. A total of 276 bird species has been recorded up to 6 April 2024 including 23 additional species found in the March 2024 survey and another 16 species located in the desk study. In 2016 BaNPBZ was assessed as an Important Bird and Biodiversity Area (IBA) based largely on the results of two surveys in 2012 and 2016, using globally threatened species and characteristic biome species criteria. Eight globally threatened species have been recorded so far including one species, great slaty woodpecker Mulleripicus pulverulentus which has significant populations in BaNPBZ, so still fulfilling the globally threatened criterion for an IBA. BaNPBZ has extensive forests in the Indo-Malayan tropical dry zone biome. It supports 69 per cent of species characteristic of this biome which have been recorded in Nepal, a larger number than found previously, so strengthening the justification of BaNPBZ as an IBA using the characteristic biome species criterion. Water shortage was identified by park staff as a major threat to wildlife. Access to the national park was limited in the March 2024 survey by the lack of a 4-wheel drive vehicle. However, the buffer zone was much easier to cover and was found to include high-quality tropical broadleaved forest and riverine habitats. Only lower altitudes up to 200 m were covered. Further bird surveys in all seasons, covering all habitats and the full altitudinal range of the park from 153-1247 m should produce many more bird species and are highly recommended.